Lifestyle factors associated with muscle quality in community‐dwelling older people with type 2 diabetes in Japan and Taiwan: a cross‐sectional study. Issue 5 (19th July 2022) - Yamaguchi, Yuko; Greiner, Chieko; Lee, Shu‐Chun; Ryuno, Hirochika; Yen, Hsin‐Yen; Lin, Chiou‐Fen; Lee, Ting‐I; Lee, Pi‐Hsia
Abstract: Background: Type 2 diabetes mellitus (T2DM), common in older people, is an important reason for muscle loss in Japanese and Taiwanese populations. However, little is known about the association between lifestyle behaviours and muscle quality. We aimed to compare the lifestyle behaviours of Japanese and Taiwanese older adults with T2DM and to the identify lifestyle factors associated with muscle quality. Methods: This cross‐sectional study was conducted among community‐dwelling individuals with T2DM aged ≥65 years in Taiwan and Japan. Totally, 114 Japanese and 226 Taiwanese participants were enrolled in the study. Outcomes were measured by blood biochemical examinations, body composition analyses and structured self‐reported questionnaires to assess lifestyle behaviours and muscle quality. Linear regression models were used to examine the relationship between lifestyle factors and muscle quality using SPSS version 27.0 with a statistical significance level of P < 0.05. Results: Japanese subjects were more likely to be smokers and alcohol consumers, and they were less likely to have well‐balanced diets and engage in more physical activity as compared to Taiwanese subjects. The muscle quality in the Japanese subjects was significantly poorer than that in the Taiwanese subjects. Physical activity, dietary habits and smoking were associated with muscle quality, after adjusting for age, gender and body mass index. Conclusions: Physical activity of insufficient intensity, unhealthy dietary habits and smoking could be risk factors for poor muscle quality. These findings can contribute to the development of effective strategies to improve muscle quality in community‐dwelling older Asian people with T2DM.